Antibacterial activity of ethanolic extract of Caesalpinia spinosa (Molina) Kuntze “tara”, Fabaceae on bacteria of the oral biofilm - Pareja-Vásquez, María (2020)
Objective: To determine the antibacterial, in vitro activity of ethanolic extract of Caesalpinia spinosa (Tara), on the oral biofilm bacteria cultures. Material and methods: An in vitro experimental study was carried out, in which the antibacterial activity of an ethanolic extract of C. spinosa and the controls (chlorhexidine 0.12%, oral antiseptic (OA), ethanol and distilled water), were compared to strain cultures strains of Streptococcus mutans (ATCC® 25175), Streptococcus sanguinis (ATCC® 10556), Enterococcus faecalis (ATCC® 29212), Staphylococcus aureus (ATCC® 6538) and Porphyromonas gingivalis (ATCC® 30277). The agar diffusion method with 6 mm diameter wells was used, with the experimental group and controls Results: It was evident that the average of the inhibition zone formed by the application of the ethanolic extract of C. spinosa on S. aureus was much larger than the one obtained with chlorhexidine 0.12% or the OA (p<0.000). Also noted, that average C. spinosa extract inhibition zone was larger than controls, against S. sanguinis (p<0.000). Conclusion: C. spinosa (Tara) showed an antibacterial activity in vitro against the presence of S. aureus, S sanguinis, S. mutans and E. faecalis. There was no inhibitory activity on P. gingivalis.